Evaluating the extent of intrapreneurship in a sugar producing company in KwaZulu-Natal, South Africa - Zyven Rambakus; Muhammad Hoque; Cecile N. Gerwel Proches (Cogent Business & Management, 2020)
The sugar industry in South Africa is currently facing immense challenges in the form of the sugar tax, growing negative consumer sentiment, climate change and cheap imported sugar. It is within this context that intrapreneurship can be embraced to inject vitality, flexibility, innovation and sustainability in firms in this sector. The objectives were to measure the intrapreneurial climate, determine its strengths and weaknesses as well as constraints, identify strategies to enhance the intrapreneurial culture and test their influence on intrapreneurial behaviour. This cross-sectional study assessed the extent of intrapreneurship in a major sugar producing company in South Africa using a sample of 110 managers and a self-administered online questionnaire. The findings revealed a low intrapreneurial climate, with the firm's weaknesses revolving around leadership style, structure, culture, systems and its core activities. Its strength lies in its managers that displayed high levels of entrepreneurial orientation. Capital availability, bureaucracy, resource availability, a poorly understood innovation process, lack of leadership style and management support were perceived as barriers. Recommendations to the firm include enhancing recognition and rewards programmes, fostering team work, cross functional communication, tapping into the talent and vision of the youth, establishing an innovation board, benchmarking through employee exchange programmes and finally, implementing training and development around entrepreneurial leadership.
Keywords: 650; Intrapreneurship; sugar industry; entrepreneurial leadership; South Africa